The Perception of the Economy and Limits, Boundaries as well as Dimensions of Economic Policy - Gylys, Povilas (Ekonomika, 2003)
Whilst discussing measures of economic policy we implicitly or explicitly base our arguments on one or another perception of the economy. Therefore this link between conceptual, theoretical, paradigmatic side of human activities on the one hand, and practical side on the other, is worthwhile to explore. It is even more the case if we concede that economic science pays little attention to the definition of the key economic concept “economy”.Author of the article argues that it is a major breakaway from classical tradition (A. Smith), which prescribes to link economic reality with flows and movement of national wealth. Defining economy as an aspect of social life reflecting the movement of wealth, author defines the latter as a combination of the private, public and natural goods. Accordingly in he discriminates between market, public and natural regimes in economy, stressing that none of them exist in their pure form.Assumption that economy encompasses the goods and regimes mentioned above, serves as a basis for wider than usual understanding of economic policy. Traditionally economic policy is understood as concerned mainly or even exclusively with production of private goods, with market Other aspects of life education, science. politics. legal sphere etc. – are assumed as external to economy. Even if they are included to the sphere of economic policy this inclusion is one-sided – only costs to society are considered and benefits are not taken into account It is serious distortion of the philosophy of economic policy. This distortion is felt especially acutely in the domain of public finances. when public sector is treated as a financial burden and when benefits (utility) produced in the public sector are taken for granted or neglected as non-economic. Such a neglect of public as well as natural goods almost unavoidably makes economic development unbalanced and unsustainable. and could be the reason for future turbulences.